Design And Building Of Web-Based Letter Archives Management In The Medan Mayor's Office - Nasywa Rizki Fatihah; Sonia Natasyah; Reqha Naqhita Iswandi; Raihan Novalda Zhafira; Darmeli Nasution (Yayasan Sinergi Multidimensi Kreatif, 2024)
This research aims to design and implement an efficient and integrated web-based mail archive management system in the Medan Mayor's Office. Research data was obtained through observation, interviews and documentation studies related to the process of managing letter archives at the Medan Mayor's Office. The result of this research is the development of a web-based letter archive management system consisting of modules for receiving letters, indexing, storing and searching letter archives. This system allows users to upload and search letters electronically, as well as manage metadata and mail history easily. Apart from that, this system also provides security features and access rights that can be configured according to user roles. This research can result in increasing the efficiency of mail archive management, reducing errors in mail searches, and increasing information accessibility for users. This research contributes to the development of an efficient and integrated mail archive management system in the government administration environment. It is hoped that this system can provide benefits in improving the performance of mail archive management at the Medan Mayor's Office and become a reference for developing similar systems in other government agencies.